Process for preparing aluminum foil for lithium battery using large crown support roller
By using a large convex support roll process in the production of aluminum foil for lithium batteries, the problems of unstable tensile strength, elongation and plate quality of aluminum foil for lithium batteries are solved, and the flatness of the plate and the material yield are improved, and the production cost is reduced.
Patent Information
- Application Number
- CN202211174907.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-26
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-09-26
AI Technical Summary
In the production of existing aluminum foil for lithium batteries, the tensile strength and elongation are difficult to meet the needs of high-end lithium batteries, the plate quality is unstable, and the surface wettability is insufficient, resulting in high production difficulty, low material yield and high production cost.
The process of supporting rolling rolls with large convexity is adopted, and high-performance aluminum foil for lithium batteries is prepared by multiple passages of rough rolling, medium rolling and finishing rolling, combined with specific rolling parameters and rolling oil components.
The flatness of the plate type has been improved. The matching degree between the actual plate type and the target plate type has reached more than 95%, the material yield has been increased by 15-20%, and the comprehensive material yield has reached more than 85%, reducing production costs.
Smart Images

Figure BDA0003863847300000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonferrous metal processing, relates to the production of aluminum foil, and in particular to a process for preparing aluminum foil for lithium batteries by using a large convex support roller. Background Art
[0002] Due to the rapid development of new energy vehicles, lithium batteries, as the core components of new energy vehicles, have a strong demand for lithium battery aluminum foil, driving the demand for battery aluminum foil to rise rapidly.
[0003] Lithium batteries are key energy storage components for new energy vehicles. Aluminum foil, as a positive electrode material, has a significant impact on the life, consistency, and rate discharge of lithium batteries. Battery foil is a deep-processed product of aluminum foil. It has many key technologies and high requirements for technical indicators. Its production difficulty is much greater than that of ordinary aluminum foil. Battery foil has very strict requirements for its various technical indicators. It is a leader in the aluminum foil family. It requires the thinnest thickness, highest strength, highest surface dyne value, smallest thickness difference, optimal plate shape, and cleanest surface, while constantly pursuing the extreme values of these six aspects. At present, aluminum foil for high-end lithium batteries usually has a double-light thickness of ≤13μm and below, and a strength of ≥250N / mm 2 From the perspective of cost performance, the thinner the better, provided that the strength is ensured; from the perspective of subsequent deep processing requirements, the plate must be flat, clean and uniform on the surface, and free of scratches and other defects. The tensile strength required for existing aluminum foil for lithium batteries is usually 190N / mm 2 The above, through multiple rolling hardening, the final product meets the tensile strength ≥ 250N / mm 2 performance requirements.
[0004] Ordinary aluminum foil for lithium batteries is mostly made by the following process: the raw aluminum foil for lithium batteries is heated and melted into an aluminum alloy melt according to a certain alloy component ratio. After smelting processes such as slag removal, grain refinement, degassing and slag removal, and filtration, the aluminum alloy melt is continuously cast and rolled through a casting and rolling mill to form an aluminum plate blank with a thickness of about 7 mm; the slab is subjected to the processes of cold rolling, crystallization annealing, cold rolling again, and finishing to obtain the blank for lithium battery aluminum foil; the aluminum foil blank is subjected to several passes of rough rolling, intermediate rolling, finish rolling, and slitting on a four-roll rolling mill to obtain a finished aluminum foil for lithium batteries.
[0005] At present, the lithium battery manufacturing industry is basically optimized on the basis of the ordinary aluminum foil rolling process, which includes: 1. Increasing the rolling pass and reducing the pass reduction rate; 2. In order to deal with work hardening, increasing the crown of the working roll; 3. In order to improve the surface wetting tension of the battery foil, the finishing rolling uses a special additive for the battery foil. The main problems are as follows:
[0006] (1) The tensile strength and elongation are difficult to meet the demand for aluminum foil for existing high-end lithium batteries. From the perspective of cost performance, thinning the thickness of lithium battery foil is conducive to reducing the cost of raw materials, but it also affects the absolute performance strength value, resulting in the market generally requiring the performance of thin lithium battery foil to be ≥250N / mm 2 , some even reach 270N / mm 2 The above has reached the strength limit of cold work hardening of aluminum foil products. At the same time, when the strength reaches a certain level, the corresponding elongation is difficult to guarantee, and the production is extremely difficult.
[0007] (2) The quality of the plate shape is unstable, and local looseness is obvious. For the subsequent deep processing of battery foil, the plate shape is a key technical indicator that affects carbon coating and energy density. With the development of the industry and the continuous improvement of the precision of lithium battery products, users will have higher and higher requirements for the plate shape of aluminum foil products. The higher the strength requirement and the thinner the thickness of the double-sided lithium battery aluminum foil, the more prominent the local plate shape defects are, which brings great quality risks to downstream battery foil users and is one of the important issues that lead to reduced battery foil quality and complaints. How to continuously improve the plate quality of products through process optimization and technological innovation is an important issue facing the aluminum foil industry.
[0008] (3) Wettability: Surface wettability is also one of the more important technical indicators of battery foil, which directly affects the adhesion quality of the coating. When the dyne value is low, the aluminum foil and the carbon-coated material are not firmly bonded, resulting in coating leakage. The dyne value of the aluminum foil surface should be greater than 32dyn / mm, and some products with high carbon coating requirements should even reach 34dyn / mm.
[0009] These problems make the production of aluminum foil for lithium batteries difficult, the overall yield rate is low, the production cost is high, and the company's development risks are increased. This is also one of the reasons why many aluminum processing companies believe it is not worth getting involved in the production of lithium battery aluminum foil. With the shift of the focus of the national energy strategy, the demand for lithium batteries for new energy vehicles has increased rapidly, and the development and production of high-quality lithium battery aluminum foil is imperative. Summary of the invention
[0010] In view of the shortcomings of the flatness of the existing aluminum foil for lithium batteries, the present invention aims to provide a process for preparing aluminum foil for lithium batteries using a large convex support roller.
[0011] A process for preparing aluminum foil for lithium batteries using a large crown support roller comprises the following steps:
[0012] 1. The battery foil raw material is subjected to several rough rolling and intermediate rolling to obtain a single aluminum foil, wherein the radial convexity of the support roller is 0.03-0.05mm larger than the radial convexity of 0.01-0.02mm of the support roller used for ordinary aluminum foil rolling, and is 0.04-0.07mm;
[0013] 2. The single aluminum foil is finely rolled on a fine rolling mill and trimmed at the same time to obtain an aluminum foil for lithium batteries of the required thickness, wherein the radial convexity of the fine rolling support roller is 0.03-0.05 mm larger than the radial convexity of 0.01-0.02 mm of the support roller used for rolling ordinary aluminum foil, that is, 0.04-0.07 mm;
[0014] 3. Slitting, corona treatment and finished product packaging to obtain the finished lithium battery foil.
[0015] In the preferred disclosed example of the present invention, the battery foil raw material hardness in step 1 is H18, and the tensile strength is ≥190 / mm 2 , elongation ≥ 3.0%, including but not limited to 1100 alloy.
[0016] In the preferred disclosed example of the present invention, the rough rolling and intermediate rolling in step one are performed on the same rolling mill, or the rough rolling and intermediate rolling can be separated, that is, the intermediate rolling process is performed on a finishing mill to further increase the wetting tension on the battery foil surface.
[0017] In the preferred disclosed example of the present invention, the battery foil raw material in step 1 is taken as an example with a thickness of 0.24±3% mm, and is subjected to 3 rough rolling passes and 1 intermediate rolling pass to a single aluminum foil of 0.016mm-0.19mm±3%, which is used to roll a 9-13μm dual-photovoltaic battery foil. The rolling pass distribution is as follows:
[0018] 0.24mm→0.12mm→0.065mm→0.033mm→0.019mm→0.13mmm,
[0019] Or 0.24mm→0.125mm→0.06mm→0.03mm→0.0175mm→0.012mm,
[0020] Or 0.24mm→0.125mm→0.06mm→0.03mm→0.016mm→0.009mm,
[0021] The parameters of the rolls used in each pass are:
[0022] The roughness of the rough rolling work roll is selected between Ra: 0.22 ~ 0.26μm, and the radial convexity is selected between Cr: 0.02 ~ 0.04mm (also marked as Cr: 20 ~ 40‰);
[0023] The roughness of the intermediate rolling work roll is selected between Ra: 0.11 ~ 0.15μm, and the radial convexity is selected between Cr: 0.02 ~ 0.06mm (also marked as Cr: 20 ~ 60‰);
[0024] The roughness of the support rolls used for rough and medium rolling is between Ra: 0.6±10%μm, and the radial convexity is selected between Cr: 0.04~0.07mm (also marked as Cr: 40~70‰);
[0025] Target plate curve value for rough and medium rolling passes ≤13N / mm 2 .
[0026] In the preferred disclosed example of the present invention, the rolling oil used in step one is a mixture of base oil + a certain proportion of alcohol and ester additives, wherein the alcohol content is about 5-7%, mainly C12 lauryl alcohol; the ester content is about 4-6%, mainly C12-14 butyl stearate.
[0027] In the preferred disclosed example of the present invention, in step 2, a single aluminum foil of 0.0175 mm ± 3% obtained by intermediate rolling is used as an example, and the roughness of the finishing rolling work roll used is Ra: 0.10 μ ± 5% m, and the radial convexity Cr: 0.05 mm;
[0028] Finishing mill support roll roughness Ra: 0.6±10%μm, radial convexity Cr: 0.06mm;
[0029] Finishing pass target plate curve value ≤ 11N / mm 2 .
[0030] In the preferred disclosed example of the present invention, the rolling oil used in step 2 is base oil + 8-10% ester additive W3, and the additive W3 is purchased from Shijiazhuang Xintai Special Oil Co., Ltd., and the main components are 80% ethyl decanoate + 20% methyl decanoate.
[0031] The selection of working roll crown varies according to the width of the raw material. The distinction between the width of the rolled material is related to the width range of the material that can be rolled by the rolling mill, and the cost, efficiency and operability of the grinding roll are taken into consideration. The definition of the width of the raw material is usually based on the middle value of the specifications that can be rolled by the rolling mill, which is convenient for distinguishing the roll crown used in the rolling process; the crown is used to compensate for the change in the disturbance of the roll under pressure, which will lead to uneven pressure in the roll gap area. Based on this, the crown selection is usually a small crown for narrow materials and a large crown for wide materials. The selection of the crown of the support roll can also vary to a certain extent according to the width of the effective working roll surface of the rolling mill. Basically, the crown of the support roll increases with the width of the rolling mill. However, for the same rolling mill, considering production efficiency, the selection of the crown of the support roll usually no longer changes with the width of the rolled material.
[0032] The selection of the crown of the working roll in step 2 is the same as the above principle.
[0033] Steps 1 and 2 use a large convex support roller, the convexity of which reaches 0.06mm (also marked as 60‰); the radial convexity of the support roller in the production process of ordinary aluminum foil is usually 0.01-0.02mm (10-20‰), and no convexity above 0.03mm has been found. This is mainly related to the characteristics of the raw material selected for battery foil. Ordinary aluminum foil is usually used as packaging material, and the finished aluminum foil is delivered in annealed and softened O state. Usually the blank is selected with hardness H14 and performance 130-150N / mm 2 , the maximum performance of aluminum foil after hardening of 1 series aluminum alloy billet usually does not exceed 200N / mm 2 In the subsequent battery manufacturing process, the battery foil needs to withstand the pressure of the lithium alloy powder of the energy-gathering material on the surface of the battery foil. The pressure of the pressure process reaches about 200t, which requires the battery aluminum foil to have a high strength (≥250N / mm 2 ) and elongation (≥2.5%) can meet the performance requirements of the above-mentioned processing process.
[0034] When the raw material properties change significantly, the biggest problem when using conventional ordinary foil small crown support rollers (Cr: 0-20‰) to produce battery foil is that the plate shape in the second step of the finishing rolling process is extremely unstable, and the actual plate shape is less than 80% consistent with the target plate shape. The finishing rolling process is difficult to roll, with many broken strips and poor yield. This leads to low production efficiency of battery foil, and the yield rate is 15-20% lower than that of ordinary foil.
[0035] The invention adopts a large crown support roller to produce high-performance battery foil, overcomes the unstable plate shape phenomenon, and the degree of consistency between the actual plate shape and the target plate shape reaches more than 95%, the comprehensive yield rate is increased to more than 85%, and the efficiency and quality have undergone qualitative changes.
[0036] The difference between the present invention and the conventional battery foil production process is that the support roller process convexity uses a large convexity, and the deflection compensation of the entire roller system is transferred to the support roller, which reduces the interference of the axial roller surface speed difference caused by the use of large convexity working rollers on the rolling stability, and is more conducive to improving the flatness of the plate shape, so that the tolerance value between the actual plate shape and the target plate shape is less than 5%, and the degree of fit reaches more than 95%. Compared with the previous process, the plate shape fit has been qualitatively improved.
[0037] In the preferred disclosed example of the present invention, the corona in step 3 belongs to the battery foil surface treatment device, which further cleans the residual oil on the surface of the aluminum foil, improves the surface cleanliness, and prevents leakage in the subsequent battery foil carbon coating process. Using a corona device with a power of 8 to 15kw and an output voltage of 25kv to perform surface corona is a common technology for improving surface wetting tension.
[0038] Beneficial Effects
[0039] The difference between the present invention and the conventional battery foil production process is that a large crown support roller is used. The high-performance battery foil produced has a conformity of more than 95% between the actual plate shape and the target plate shape (the plate shape tolerance requires a sigma value of less than 5%), and the yield rate is increased by 15-20%, and the comprehensive yield rate reaches more than 85%. At the same time, the rolling process is continuous and stable, which improves production efficiency and quality, reduces the production cost of battery foil, and is the most potential benefit growth point in the future, providing solid technical support for high-quality large-scale production of battery foil. DETAILED DESCRIPTION
[0040] The present technology is described in detail below in conjunction with embodiments so that those skilled in the art can better understand the present technology, but the present technology is not limited to the following embodiments.
[0041] Example 1
[0042] A production process for preparing double-light 12μm aluminum foil for lithium batteries using a large crown support roller comprises the following steps:
[0043] Step 1: Rough and medium rolling
[0044] The raw material of alloy 1100H18 with a thickness of 0.24×1200㎜ was subjected to three rough rolling and one intermediate rolling to a single foil of 0.0175mm±3%, and the tensile strength of the raw material was measured to be 193N / mm 2 , extended by 4.5%;
[0045] Finished product quality requirements: thickness 12μm±3%, tensile strength ≥250N / mm 2 , elongation ≥ 3.0%, surface dyne value ≥ 32dyn; flat plate shape, offline plate shape A grade (roller distance 2m, tension 0.8kg / mm 2 ) collapse ≤5mm; surface color is uniform and clean; number of pinholes below 0.1mm ≤20 / m 2 .
[0046] Rolling pass distribution: 0.24mm→0.125mm→0.06mm→0.03mm→0.0175mm→0.012mm;
[0047] The roller parameters used in step 1 are as follows:
[0048] The working roll roughness Ra used in rough rolling 1-3 passes: 0.24±5%μm, radial crown Cr: 0.030mm (30‰);
[0049] The roughness of the working roll in the 4th pass is Ra: 0.13±5%μm, and the radial crown is Cr: 0.03mm (30‰);
[0050] The roughness of the support rolls used for rough and medium rolling is Ra: 0.6±10%μm, and the radial convexity Cr is 0.06mm (60‰);
[0051] Target profile curve value for rough and medium rolling passes: 13N / mm 2 ;
[0052] The rolling oil is a lubricant that is evenly mixed with 80# base oil, 5% ester additives, and 5% alcohol additives.
[0053] During the rough and medium rolling process, the plate shape is stable, the actual plate shape matches the target plate shape by 98%, the whole coil is produced without broken strips, and the surface quality is good;
[0054] Step 2: Roll the obtained single aluminum foil on a finishing mill for the fifth time and trim the edges at the same time to obtain the battery aluminum foil with the required thickness of the finished product; 0.0175mm→0.012mm;
[0055] The roughness of the finishing roller used is Ra: 0.10μm±5%. As wide material, the convexity is selected as Cr: 0.06mm (60‰);
[0056] The roughness of the support roll used for finishing rolling is Ra: 0.6±10%μm, and the radial convexity Cr is 0.06mm (60‰);
[0057] The target plate shape curve value of the finishing pass is set to 11N / mm2;
[0058] The rolling oil uses 80# base oil + 8-10% additive W3 mixed oil as lubricating oil;
[0059] The actual plate shape during the finishing production process is consistent with the target plate shape by 97%. The plate shape is stable during the production process, there is no broken strip, the surface quality is good, the measured surface wetting tension of the blank is 31dyn, the measured thickness is 12.15μm, the tensile strength is 258N / ㎜2, the elongation is 3.25%, and the number of pinholes is less than 10 / m 2 , the finishing rolling inspection meets the quality requirements of battery foil.
[0060] Step 3: Slitting, corona treatment and finished product packaging.
[0061] The battery foil produced in step 2 above has a flat plate shape and uniform surface waves during the slitting process of the slitting machine, without loose ribs or local looseness. The standard offline plate shape detection has a collapsed edge of ≤5mm, which can reach Class A plate shape according to industry standards and fully meet the battery foil shape quality requirements.
[0062] During the slitting corona process, the corona power parameters of the upper and lower aluminum foil surfaces are 8.8kw / 8.8KW, the slitting speed is 120m / mN / ㎜2n, and the actual upper and lower surface wetting tension is 33dyn, which meets the surface wetting tension requirements of the battery foil.
[0063] Example 2
[0064] A production process for preparing double-light 9μm aluminum foil for lithium batteries using a large crown support roller, comprising the following steps:
[0065] Step 1: Rough and medium rolling
[0066] The raw material of alloy 1100H18, thickness 0.24mm×1100㎜, was subjected to three rough rolling and one intermediate rolling to a single foil of 0.016mm±3%, wherein the raw material tensile strength was measured to be 196N / ㎜2, and the elongation was 4.1%;
[0067] Finished product quality requirements: thickness 9μm±3%, tensile strength ≥250N / ㎜2, elongation ≥2.0%; surface dyne value ≥32dyn; thickness 12μm±3%, tensile strength ≥250N / mm 2 , elongation ≥ 3.0%, surface dyne value ≥ 32dyn; flat plate shape, offline plate shape A grade (roller distance 2m, tension 0.8kg / mm 2 ), collapse ≤5mm; surface color is uniform and clean; number of pinholes below 0.1mm ≤30 / m 2 .
[0068] Rolling pass distribution: 0.24mm→0.125mm→0.06mm→0.03mm→0.016mm→0.009mm;
[0069] The roller parameters used in step 1 are as follows:
[0070] The working roll roughness Ra used in rough rolling 1-3 passes: 0.24±5%μm, radial crown Cr: 0.03mm (30‰);
[0071] The roughness of the working roll in the 4th pass is Ra: 0.13±5%μm, and the radial crown is Cr: 0.03mm (30‰);
[0072] The radial crown of the support roll used for roughing and medium rolling is Cr: 0.06mm (60‰), and the roughness of the support roll is Ra: 0.6±10%μm;
[0073] Target profile curve value for rough and medium rolling passes: 13N / mm 2 ;
[0074] The rolling oil is a lubricant that is evenly mixed with 80# base oil, 5% ester additives, and 5% alcohol additives.
[0075] During the production process of this step, the plate shape is stable, the actual plate shape matches the target plate shape by more than 96%, and the surface quality is good;
[0076] Step 2: Roll the obtained aluminum foil with a thickness of 0.016 mm on a finishing mill for the fifth pass, and trim the edges by 10 mm each to obtain a finished aluminum foil for batteries with a thickness of 9 um; the pass is 0.016 mm → 0.009 mm;
[0077] The roughness of the finishing roller used is Ra: 0.07 ± 5% μm, and the convexity is selected as Cr: 0.06 mm (60‰);
[0078] The roughness of the support roll used in the finishing mill is Ra: 0.6±10%μm, and the radial convexity of the support roll is Cr: 0.06mm (60‰);
[0079] The target profile curve value for the finishing pass is set to 11N / mm 2 ;
[0080] The rolling oil is a rolling lubricant oil obtained by mixing 80# base oil and 8-10% additive W3 evenly.
[0081] During the finishing rolling process, the actual plate shape matches the target plate shape by more than 95%, the production process is stable without strip breakage, and the coiling surface quality is good. The measured surface wetting tension of the material is 31dyn. The measured thickness is 9.15μm and the tensile strength is 255N / mm 2 , elongation 3.05%, less than 0.1mm pinhole number <20 / m 2 , meeting the quality requirements of battery foil.
[0082] Step 3: Slitting, corona treatment and finished product packaging.
[0083] The battery foil produced in step 2 is cut by the slitting machine. The online foil surface is flat and the overall wave is uniform. The offline foil detection reaches Class A (roller distance 2m, tension 0.8kg / mm 2 ), the actual maximum depression of 4.8mm occurs in the ribs, and the depression is ≤5mm. According to industry standards, it can reach Class A plate type and meet the quality requirements of battery foil plate type.
[0084] During the slitting corona process, the corona power parameters of the upper and lower aluminum foil surfaces are 8.8kw / 8.8KW, the slitting speed is 120m / mN / ㎜2n, and the actual wetting tension of the upper and lower surfaces is the same, both reaching 33dyn, which meets the surface wetting tension requirements of the battery foil.
[0085] Example 3
[0086] A production process for preparing double-light 13μm aluminum foil for lithium batteries using a large crown support roller comprises the following steps:
[0087] Step 1: Rough and medium rolling
[0088] The raw material of alloy 1100H18 with a thickness of 0.24×1200㎜ was subjected to three rough rollings and one intermediate rolling to a single foil of 0.019mm±3%, and the tensile strength of the raw material was measured to be 193N / mm 2 , extended by 4.5%;
[0089] Finished product quality requirements: thickness 3μm±3%, tensile strength ≥240N / mm 2 , elongation ≥ 3.0%, surface dyne value ≥ 32dyn; flat plate shape, offline plate shape A grade (roller distance 2m, tension 0.8kg / mm 2 ) collapse ≤5mm; surface color is uniform and clean; number of pinholes below 0.1mm ≤10 / m 2 .
[0090] Rolling pass distribution: 0.24mm→0.125mm→0.065mm→0.033mm→0.019mm→0.013mm;
[0091] The roller parameters used in step 1 are as follows:
[0092] The working roll roughness Ra used in rough rolling 1-3 passes: 0.24±5%μm, radial crown Cr: 0.030mm (30‰);
[0093] The roughness of the working roll in the 4th pass is Ra: 0.13±5%μm, and the radial crown is Cr: 0.03mm (30‰);
[0094] The roughness of the support rolls used for rough and medium rolling is Ra: 0.6±10%μm, and the radial convexity Cr is 0.06mm (60‰);
[0095] Target profile curve value for rough and medium rolling passes: 13N / mm 2 ;
[0096] The rolling oil is a lubricant that is evenly mixed with 80# base oil, 5% ester additives, and 5% alcohol additives.
[0097] During the rough and medium rolling process, the plate shape is stable, the actual plate shape matches the target plate shape by 98%, the whole coil is produced without broken strips, and the surface quality is good;
[0098] Step 2: Roll the obtained single aluminum foil on a finishing mill for the fifth time and trim the edges at the same time to obtain the battery aluminum foil with the required thickness of the finished product; 0.019mm→0.012mm;
[0099] The roughness of the finishing roller used is Ra: 0.10μm±5%. As wide material, the convexity is selected as Cr: 0.06mm (60‰);
[0100] The roughness of the support roll used for finishing rolling is Ra: 0.6±10%μm, and the radial convexity Cr is 0.06mm (60‰);
[0101] The target profile curve value for the finishing pass is set to 11N / mm 2 ;
[0102] The rolling oil uses 80# base oil + 8-10% additive W3 mixed oil as lubricating oil;
[0103] The actual plate shape during the finishing rolling production process is consistent with the target plate shape by 97%. The plate shape is stable during the production process, there is no broken strip, the surface quality is good, the measured surface wetting tension of the blank is 31dyn, the measured thickness is 12.15μm, and the tensile strength is 249N / mm 2 , elongation 3.55%, number of pinholes <10 / m 2 , the finishing rolling inspection meets the quality requirements of battery foil.
[0104] Step 3: Slitting, corona treatment and finished product packaging.
[0105] The battery foil produced in step 2 above has a flat plate shape and uniform surface waves during the slitting process of the slitting machine, without loose ribs or local looseness. The standard offline plate shape detection has a collapsed edge of ≤5mm, which can reach Class A plate shape according to industry standards and fully meet the battery foil shape quality requirements.
[0106] During the slitting corona process, the corona power parameters of the upper and lower aluminum foil surfaces are 8.8kw / 8.8KW, the slitting speed is 120m / mN / ㎜2n, and the actual upper and lower surface wetting tension is 33dyn, which meets the surface wetting tension requirements of the battery foil.
[0107] Comparative Example 1
[0108] Conventional aluminum foil rolling process, using a small convex support roller to prepare a double-light 12μm aluminum foil for lithium batteries, includes the following steps:
[0109] Step 1: Rough and medium rolling
[0110] The raw material of alloy 1100H18 and thickness of 0.24×1200mm was subjected to three rough rolling and one intermediate rolling to a single foil of 0.0175mm±3%. The raw material was the same as the raw material used in Example 1 and was produced by the same manufacturer and the same batch. The tensile strength of the raw material was measured to be 195N / mm 2 , extended by 4.15%;
[0111] Finished product quality requirements: thickness 12μm±3%, tensile strength ≥250N / mm 2 , elongation ≥3.0%; surface dyne value ≥32dyn; flat board shape without obvious local looseness, offline collapse detection ≤5mm (A grade or above); surface color is uniform and clean; number of pinholes below 0.1mm ≤20 / m 2 .
[0112] Rolling pass distribution: 0.24mm→0.125mm→0.06mm→0.03mm→0.0175mm→0.012mm;
[0113] The parameters of the rollers used are:
[0114] The working roll roughness Ra used in rough rolling 1-3 passes: 0.24±5%μm, radial crown Cr: 0.050mm (50‰);
[0115] The roughness of the working roll in the 4th pass is Ra: 0.13±5%μm, and the radial crown is Cr: 0.050mm (50‰);
[0116] The radial crown Cr of the support roll used for roughing and medium rolling is 0.02mm (20‰), and the roughness Ra of the support roll is 0.6±10%μm;
[0117] Target profile curve value for rough and medium rolling passes: 13N / mm 2 ;
[0118] The rolling oil is a lubricant that is evenly mixed with 80# base oil, 5% ester additives, and 5% alcohol additives.
[0119] During the production process of this step, the board shape feedback showed that the ribs and edges were obviously loose, and the actual board shape matched the target board shape by about 90%. There was no broken belt during the production process and the surface quality was good.
[0120] Step 2: Roll the obtained 0.0175mm single zero aluminum foil on the finishing mill for the fifth time, and trim the edges by 10mm at the same time to obtain the battery aluminum foil with the required thickness of the finished product; 0.0175mm→0.012mm;
[0121] The roughness of the finishing roller used is Ra: 0.10 ± 5% μm. As a wide material, the convexity is selected as Cr: 0.07 mm (70‰);
[0122] The roughness of the support roll used in the finishing mill is Ra: 0.6±10%μm, and the radial convexity of the support roll is Cr: 0.02mm (20‰);
[0123] The target profile curve value for the finishing pass is set to 11N / mm 2 ;
[0124] The rolling oil uses 80# base oil + 8-10% additive W3 mixed oil as lubricating oil.
[0125] During the finishing rolling production process, the actual plate shape is poorly consistent with the target plate shape, and the plate shape tolerance sigma shows more than 25% (which means that the actual plate shape is less than 75% consistent with the target plate shape). The production process is mainly characterized by large changes in plate shape, which are mainly manifested in severe loose ribs, loose edges, and tightness in the middle. The coiled material surface is prone to wrinkling and softening, making it difficult to stabilize normal production, which is significantly different from Examples 1 and 2. The measured surface wetting tension of the blank is 30dyn. The measured thickness is 12.15μm and the tensile strength is 258N / mm 2 , elongation 2.85%, number of pinholes> 30 / m 2 .
[0126] Since this comparative example failed to produce qualified battery foil, step three could not be carried out normally.
[0127] Comparative Example 2
[0128] Comparative Example 1 still cannot explain the advantages and disadvantages of the small crown support roll process and the large crown process. According to the plate shape performance during the production process of Comparative Example 1, the production process of the double-light 12μm lithium battery aluminum foil after adjusting the crown of the working roll includes the following steps:
[0129] Step 1: Rough and medium rolling
[0130] The raw material of alloy 1100H18 and thickness of 0.24×1200mm was subjected to three rough rolling and one medium rolling to a single foil of 0.0175mm±3%. The raw materials were the same as the raw materials used in Examples 1 and 3, from the same manufacturer and the same batch;
[0131] The tensile strength of the wool material was measured to be 195N / ㎜2, with an elongation of 4.1%;
[0132] Finished product quality requirements: thickness 12μm±3%, tensile strength ≥250N / mm 2 , elongation ≥3.0%; surface dyne value ≥32dyn; flat plate shape without obvious local looseness, offline plate shape collapse detection ≤5mm (A grade or above); no oil on the surface; less than 0.1, mm pinhole number ≤20 / m 2 ;
[0133] The rolling passes are distributed as follows: 0.24mm→0.125mm→0.06mm→0.03mm→0.0175mm→0.012mm;
[0134] The parameters of the rollers used are:
[0135] The roughness of the working roll used in the rough rolling 1-3 passes remains unchanged Ra: 0.24±5%μm. According to the comparative example 1, the rolled plate shape is loose ribs and tight edges, and the W-plate shape is obvious, so the convexity of the working roll is prepared. This comparative example 2 is increased from 50‰ to 60‰ (Cr: 0.06mm); the production process is characterized by loose ribs and tight edges, and no other obvious defects; the overall statistical data shows that the plate shape match is less than 95%.
[0136] The roughness of the working roll of the 4th pass of the intermediate rolling is Ra: 0.13±5%μm. Since the ribs of the rolled plate in comparative example 1 are obviously loose, the convexity of the intermediate rolling working roll in this comparative example is Cr: 0.060mm (increased from 50‰ to 60‰). During the production process, the plate type is still displayed as loose ribs and tight edges. The tolerance value between the actual plate type and the target plate type exceeds 10%, which is equivalent to a fit of less than 90%. Manually increase the rolling force, increase the negative bending roll force intervention to appear obvious rib looseness;
[0137] The convexity Cr of the support roller used is 0.02mm (20‰), and the roughness Ra of the support roller is 0.6±10%μm, which remain unchanged;
[0138] Target profile curve value for rough and medium rolling passes: 13N / mm 2 .
[0139] The rolling oil is a lubricant that is evenly mixed with 80# base oil, 5% ester additives, and 5% alcohol additives.
[0140] Step 2: Roll the obtained 0.0175mm single piece material on the finishing mill for the fifth time, and trim the edges by 10mm to obtain the battery aluminum foil with the required thickness of the finished product; 0.0175mm→0.012mm;
[0141] The roughness of the finishing roll used is Ra: 0.10 ± 5% μm, and the convexity is selected as Cr: 0.07 mm (increased from 60‰ in Examples 1 and 2 to 70‰);
[0142] The roughness of the support roll used in the finishing mill is Ra: 0.6±10%μm, and the radial convexity of the support roll is Cr: 0.02mm (20‰);
[0143] The target plate shape curve value of the finishing pass is set to 11N / mm2.
[0144] The rolling oil uses 80# base oil + 8-10% additive W3 mixed oil as lubricating oil.
[0145] When the finishing rolling machine was just started, the two ribs were loose, the two sides were wrinkled, the bottoming was difficult, and the bottoming and starting failed many times. After starting, the coiling bottoming was wrinkled a lot, and the bottoming waste was seriously exceeded. During the production process, the actual plate shape showed a poor match with the target plate shape, the plate shape tolerance sigma exceeded 25%, and the overall plate shape showed loose ribs and unstable plate shape. The coiling material surface was wrinkled and soft, and it was difficult to stabilize normal production, which was significantly different from Examples 1 and 2.
[0146] After the production was less than 500kg, the machine was stopped because the plate ribs were loose and wrinkled and could not be eliminated. The material was checked: the measured thickness was 12.15μm and the tensile strength was 258N / mm 2 , elongation 2.85%, number of pinholes> 30 / m 2 The aluminum foil produced cannot meet the quality requirements of battery foil.
[0147] Since the comparative example 2 failed to produce qualified battery foil, step 3 could not be performed normally.
[0148] Comparative Example 3
[0149] Comparative Example 2 increases the convexity of the working roll on the basis of the convexity of Comparative Example 1. In order to further illustrate the advancement of the present invention through comparison, Comparative Example 3 further illustrates the difference between the small convexity process and the large convexity process of the support roll through process tests on the basis of the plate characteristics of the process tests of Comparative Examples 1-2. The trial production of Comparative Example 2 shows that the ribs are still loose even when the convexity of the working roll is increased, and the edge is not tight yet. Therefore, this comparative example adopts the method of continuing to increase the convexity of the working roll to improve the rib looseness, and continues to verify and compare the production of the large convexity support roll of the aluminum foil for the double-light 12μm lithium battery, including the following steps:
[0150] Step 1: Rough and medium rolling
[0151] The raw material of alloy 1100H18 and thickness of 0.24×1200 mm was subjected to three rough rolling and one medium rolling to a single foil of 0.0175 mm±3%. The raw materials were the same as those used in the above embodiments and comparative examples, and were from the same manufacturer and the same batch.
[0152] Finished product quality requirements: same as above
[0153] Rolling pass distribution: 0.24mm→0.125mm→0.06mm→0.03mm→0.0175mm→0.012mm;
[0154] The parameters of the rollers used are:
[0155] The roughness of the working roll used in the rough rolling 1-3 passes remains unchanged Ra: 0.24±5%μm. According to the loose edge and loose rib of the rolled plate in comparative example 2, the crown of the working roll is increased to Cr: 0.07mm (from 60‰ to 70‰); the production process is tight at the edge and loose in the middle; the rolling force and bending roll parameters are adjusted, and the edge is slightly tight and the middle is loose. The tight edge situation is strengthened after half of the production, and the production speed needs to be reduced. The plate tolerance is greater than 10%, and the fit is less than 90%. The rough rolling pass is slightly better than that of comparative example 2.
[0156] The roughness of the intermediate rolling working roll in the 4th pass is Ra: 0.13±5%μm. Since the rolled plate shape in comparative example 2 is obviously loose at the edges and loose at the ribs, the convexity of the intermediate rolling working roll is also increased to Cr: 0.070mm (from 60‰ to 70‰); during the production process, the plate shape shows loose in the middle and tight at the edges, the plate shape tolerance is greater than 10%, and the actual plate shape is about 90% consistent with the target plate shape.
[0157] The crown of the support roll used in the rough and medium rolling is Cr: 0.02mm (20‰), and the roughness of the support roll is Ra: 0.6±10%μm, which remains unchanged.
[0158] Target profile curve value for rough and medium rolling passes: 13N / mm 2 ;
[0159] The rolling oil is a mixture of 80# base oil + 5% ester additive + 5% alcohol additive evenly mixed as lubricant;
[0160] Step 2: Roll the obtained 0.0175mm single zero aluminum foil on a finishing mill for the fifth time, and trim the edges by 10mm at the same time, and produce a dual photovoltaic cell foil according to 0.0175mm→0.012mm;
[0161] The roughness of the finishing roller used in this step is Ra: 0.10 ± 5% μm. Since the middle of the incoming material is loose, the convexity is selected as Cr: 0.07 mm (the finishing pass is consistent with Comparative Example 2);
[0162] The roughness of the support roll used in the finishing mill is Ra: 0.6±10%μm, and the radial convexity of the support roll is Cr: 0.02mm (20‰);
[0163] The target profile curve value for the finishing pass is set to 11N / mm 2 ;
[0164] The rolling oil uses 80# base oil + 8-10% additive W3 mixed oil as lubricating oil.
[0165] During the finishing rolling process, the bottom edge wrinkles, the speed is difficult to start, and the coiling bottom is thick after starting. The actual plate shape shows that the ribs are loose and the middle is loose, showing an obvious M plate shape. After a period of production, the M plate shape has not improved, the overall plate shape is loose in the ribs and the middle is loose, the coiling surface is obviously barred, the plate shape tolerance sigma value exceeds 25%, and the actual plate shape is less than 80% consistent with the target plate shape.
[0166] Due to obvious stripping on the material surface, the plate shape showed no obvious improvement after producing 1 ton, so production was stopped. Unloaded material inspection: thickness 12.25μm, tensile strength 253N / mm 2 , elongation 2.85%, surface wetting tension 31dyn.
[0167] Step 3: Slitting, corona treatment, and finished product packaging
[0168] The battery foil produced in step 2 is inspected on the unwinding side of the slitting machine: there is an obvious soft bar in the middle of the foil surface, which cannot be eliminated after unfolding, the ribs on both sides are obviously loose, and the overall shape is poor. According to industry standards, the shape of the entire sheet can only reach below grade B.
[0169] Comparison table of data for each case
[0170]
[0171] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A process for preparing aluminum foil for lithium batteries using a large crown support roller, characterized in that: The steps include:
1. The battery foil raw material is subjected to several rough rolling and intermediate rolling to obtain a single aluminum foil, wherein the radial convexity of the support roller is 0.03-0.05mm larger than the radial convexity of 0.01-0.02mm of the support roller used for ordinary aluminum foil rolling, and is 0.04-0.07mm; 2. The single aluminum foil is finely rolled on a fine rolling mill and trimmed at the same time to obtain an aluminum foil for lithium batteries of the required thickness, wherein the radial convexity of the fine rolling support roller is 0.03-0.05 mm larger than the radial convexity of 0.01-0.02 mm of the support roller used for rolling ordinary aluminum foil, that is, 0.04-0.07 mm; 3. Slitting, corona treatment and finished product packaging to obtain the finished lithium battery foil.
2. The process for preparing aluminum foil for lithium batteries by using a large crown support roller according to claim 1, characterized in that: The battery foil material hardness in step 1 is H18, and the tensile strength is ≥190 / mm 2 , elongation ≥3.0%, including but not limited to 1100 alloy.
3. The process for preparing aluminum foil for lithium batteries by using a large crown support roller according to claim 1, characterized in that: The rough rolling and intermediate rolling in step 1 are carried out on the same rolling mill, or the rough rolling and intermediate rolling are separated, that is, the intermediate rolling process is carried out on a finishing mill, so as to increase the wetting tension of the battery foil surface.
4. The process for preparing aluminum foil for lithium batteries by using a large crown support roller according to claim 1, characterized in that: The battery foil raw material described in step 1 takes the thickness of 0.24±3%㎜ as an example, and is subjected to 3 rough rolling passes and 1 intermediate rolling pass to a single aluminum foil of 0.016mm~0.19mm±3%, which is used to roll 9~13μm dual photovoltaic battery foil. The rolling pass distribution is as follows: 0.24mm→0.12mm→0.065mm→0.033mm→0.019mm→0.13mmm, 0.24mm→0.125mm→0.06mm→0.03mm→0.0175mm→0.012mm, 0.24mm→0.125mm→0.06mm→0.03mm→0.016mm→0.009mm, The parameters of the rolls used in each pass are: The roughness of the rough rolling work roll is selected between Ra: 0.22 ~ 0.26μm, and the radial crown is selected between Cr: 0.02 ~ 0.04mm; The roughness of the intermediate rolling work roll is selected between Ra: 0.11 ~ 0.15μm, and the radial crown is selected between Cr: 0.02 ~ 0.06mm; The roughness of the support rolls used for rough and medium rolling is Ra: between 0.6±10%μm, and the radial convexity is selected as Cr: 0.04~0.07mm; Target plate curve value for rough and medium rolling passes ≤13N / mm 2 .
5. The process for preparing aluminum foil for lithium batteries by using a large crown support roller according to claim 1, characterized in that: The rolling oil used in step 1 is a mixture of base oil and a certain proportion of alcohol and ester additives, wherein the alcohol content is 5-7%, mainly C12 lauryl alcohol; the ester content is 4-6%, mainly C12-14 butyl stearate.
6. The process for preparing aluminum foil for lithium batteries by using a large crown support roller according to claim 1, characterized in that: In step 2, a single aluminum foil of 0.0175 mm ± 3% obtained by intermediate rolling is taken as an example. The roughness of the finishing rolling work roll used is Ra: 0.10 μm ± 5%, and the radial convexity Cr is 0.05-0.06 mm; the roughness of the support roll is Ra: 0.6 ± 10% μm, and the radial convexity Cr is 0.04-0.07 mm. The target plate curve value of the finishing rolling pass is ≤ 11 N / mm 2 .
7. The process for preparing aluminum foil for lithium batteries by using a large crown support roller according to claim 1, characterized in that: The rolling oil used in step 2 is base oil + 8-10% ester additive W3.
Citation Information
Patent Citations
Method for eliminating roller end compression of rollers of four-roller cold-rolling mill
CN106734218A
Production technology for preparing aluminum foil for lithium batteries by means of high-hardness rolls
CN111438187A